THE PORTRAIT OF SWEARWORDS AND THE SOCIAL BACKGROUND OF THE CHARACTERS IN THE BREAKFAST CLUB MOVIE - AMALIA MAULIDIATSANI, RIZKY (Language Horizon: Journal of Language Studies, 2015)
Abstrak Mengumpat adalah salah satu fenomena linguistik yang sering ditampilkan melalui berbagai media seperti majalah, koran, iklan, dan film; mengingat hal tersebut sudah cukup umum terjadi meski kadang masih dianggap hal yang tabu dan menyimpang dari norma sosial. Latar belakang sosial dapat memengaruhi terjadinya fenomena mengumpat pada masing-masing individu. Salah satu film yang dapat menggambarkan fenomena mengumpat yang berhubungan dengan latar belakang sosial adalah The Breakfast Club, karya John Hughes pada tahun 1985. <p class="MsoNormal" style="margin-left: 1.0cm; text-align: justify; tab-stops: 18.0pt 36.0pt 54.0pt 72.0pt 90.0pt 108.0pt 126.0pt 144.0pt 162.0pt 180.0pt 198.0pt 216.0pt 234.0pt 252.0pt 270.0pt 288.0pt 306.0pt 324.0pt 342.0pt 360.0pt 378.0pt 396.0pt 414.0pt 432.0pt 450.0pt 468.0pt 486.0pt 504.0pt 522.0pt 540.0pt 558.0pt 576.0pt; mso-layout-grid-align: none; text-autospace: none;">Penelitian ini difokuskan pada perbandingan kebiasaan mengumpat oleh dua tokoh yang berbeda latar belakang yang dikorelasikan dengan tujuan untuk menunjukkan pengaruh latar belakang sosial terhadap kebiasaan mengumpat. Tujuan penelitian ini adalah (1) mengetahui jenis umpatan yang diucapkan oleh tokoh dengan karakteristik tertentu (2) mengetahui bagaimana kebiasaan mengumpat seseorang dapat menggambarkan latar belakang sosialnya. Penelitian ini menggunakan metode penelitian deskriptif kualitatif, dengan menggunakan teori utama oleh Steven Pinker (2007) dan Magnus Ljung (2011), serta teori tentang neo-psycho-sociocultural of cursing oleh Timothy Jay (2000). Analisis data memerlukan proses (1) klasifikasi data berdasarkan tokoh dan (2) diskusi penggambaran umpatan yang dihubungkan dengan latar belakang sosial. Hasil menunjukkan bahwa perilaku orang tua terhadap tokoh memengaruhi pembentukan karakter dan perilaku mengumpat mereka. Umpatan yang diucapkan Bender cenderung berupa abusive dan dysphemistic swearing, sedangkan umpatan oleh Brian cenderung berupa emphatic dan idiomatic swearing. Kesimpulannya, permasalahan tokoh dalam film yang umumnya disebabkan oleh orangtua mereka membentuk pribadi mereka dan memicu mereka untuk mengucapkan kata kotor seperti fuck you, shit, asshole, fuckin’, dan bitch dan dapat menerangkan perbedaan latar belakang sosial yang berpengaruh pada cara mengumpat mereka. Kata kunci: umpatan, latar belakang sosial, latar belakang keluarga, perlakuan orangtua, film The Breakfast Club Abstract <p class="MsoNormal" style="margin-left: 1.0cm; text-align: justify; tab-stops: 18.0pt 36.0pt 54.0pt 72.0pt 90.0pt 108.0pt 126.0pt 144.0pt 162.0pt 180.0pt 198.0pt 216.0pt 234.0pt 252.0pt 270.0pt 288.0pt 306.0pt 324.0pt 342.0pt 360.0pt 378.0pt 396.0pt 414.0pt 432.0pt 450.0pt 468.0pt 486.0pt 504.0pt 522.0pt 540.0pt 558.0pt 576.0pt; mso-layout-grid-align: none; text-autospace: none;">Swearing is a linguistic phenomenon which is frequently showed in various media such as magazines, newspapers, advertisement, and movie; regarding that it happens commonly in spite of its taboo sense and referring to social norm deviation. Social background can affect the phenomenon of swearing towards respective individual. The Breakfast Club is a 1985 movie by John Hughes which can portray the swearing phenomena that is related to the social background. This study is focused on the comparison of the two main characters who have different social background one another, which is correlated to the aim of showing the influence of social background towards the swearing habit. The aim of this study consists of (1) to find out the type of swearwords based on its functions which is uttered by the specific characters (2) to find out how one’s swearing habit can portray his/her social background. This study used the descriptive qualitative method, with the theory of Steven Pinker (2007) and Magnus Ljung (2011), also the theory of neuro-psycho-sociocultural of cursing by Timothy Jay (2000). The data analysis needed process of (1) data classification per character and (2) the discussion of swearing depiction that is related to the social background. The result showed that the social background and the parenting style affects the characteristics building of the two characters and it plays role in their swearword utterance. Likewise, the character of Bender, who comes from working-class family background (lower class), tends to swear more than the character of Brian, who comes from high class family background (upper class). Bender’s swearword utterances tend to be abusive and dysphemistic swearing, while Brian’s swearword utterances tend to be emphatic and idiomatic swearing. All in all, the characters’ problems that are mostly caused by their parent shapes their personality and triggers them to utter swearwords like fuck you, shit, asshole, fuckin’, and bitch, and it can also portray their different social background that affects their swearing habit. Key words: swearword, social background, family background, parenting style, The Breakfast Club movie